Effect of the combination of superchilling and super-chilled storage on shelf-life and bacterial community dynamics of beef during long-term storage. (October 2022) - Chen, Xue; Dong, Pengcheng; Li, Ke; Zhu, Lixian; Yang, Xiaoyin; Mao, Yanwei; Niu, Lebao; Hopkins, David L.; Luo, Xin; Liang, Rongrong; Zhang, Yimin
Abstract: This study investigated the effect of superchilling (−30 °C until the core temperature achieved −3 °C, and − 1 °C until 24 h, SC) on shelf-life and bacterial community dynamics of beef loins, with a typical very fast chilling (−30 °C until the core temperature achieved 0 °C, and − 1 °C until 24 h, VFC) and conventional chilling (0– 4 °C for 24 h, CC) as controls. The super-chilled storage (−1 °C) was adopted after each chilling procedure, and physicochemical traits and microbiological quality were evaluated during a long-term storage. No remarkable adverse impact on meat color and lipid oxidation were observed in SC treatment. The bacterial composition results showed that Carnobacterium spp. were the main bacteria in SC treatment in the late storage period (63– 84 days). The loss of Lactobacillus spp., due to the "ultra-low temperature" during the superchilling, might be the reason that the SC did not result in a longer shelf-life compared with CC samples. Highlights: The SC (−30 °C until the core temperature reached −3 °C within 5 h) was applied on the beef loins. The effect of SC and the following superchilled storage on the shelf life of beef loins was studied. SC was more superior in decreasing the initial bacterial load than VFC treatment. The shelf-life of SC samples was longer than VFC samples. The loss of Lactobacillus spp. in SC samples might cause the similar shelf-life of SC and CC samples.